New electrode material β-FeOOH for aqueous rechargeable batteries - Ng, Ming Xuan (2018)
β-FeOOH electrode materials were synthesized in a bid to ascertain their electrochemical performance (cyclic voltammetry & galvanostatic cycle) for use as batteries electrodes. β-FeOOH samples were synthesized via hydrolysis technique with the aid of heating it in the oven at 100C for 24 hours. Equivalent concentration of β-FeOOH were synthesized by using precursor materials such as FeCl3, H2O and LiOH. TEM characterisation results have shown that β-FeOOH nanorods were synthesized with a diameter size distribution of 5.2 +/- 0.8nm. CV was conducted using a 3-electrode system with varying concentration (0.1M, 1M & 6M) of KOH electrolyte or 0.5M of K2SO4. CV results of KOH system were observed to have a highest peak intensity at the first cycle and decline significantly over cycle period. Peaks were observable at a relatively same position (potential). Increasing concentration of KOH causes a peak shift to left (to lower potentials). CV results of K2SO4 system were observed to obey the same trend as KOH system however, there were 2 noticeable peaks as the potential is ramped in the reversed direction. GC results of KOH system were found to have the highest specific capacity at the first cycle and drops as cycle proceeds. It was also observed that specific capacity has a larger reduction in the earlier cycles than the latter cycles. Increasing KOH concentration does not yield an observable trend. GC results of K2SO4 system were also found to obey a similar trend as KOH system however, the specific capacity decays at a much slower rate than KOH system.